UNDERSTANDING AND IMPLEMENTATION OF DIFFERENTIATED INSTRUCTION BY ENGLISH TEACHERS AT VOCATIONAL HIGH SCHOOLS IN PARIAMAN - Risnada, Risnada; Tiarina, Yuli (English Review: Journal of English Education, 2024)
Abstract: For the past four years, English teachers in Indonesia have been required to adopt Differentiated Instruction in their lessons to make their learning more adaptable for students' needs as a result of modifications to a new curriculum known as Merdeka Curriculum. However, there were limited studies conducted to investigate English teachers’ understanding and implementation of Differentiated Instruction at vocational high schools’ level. The purpose of this research is to fill this gap through qualitative research. This study is intended: (1) to investigate English teachers’ understanding of Differentiated Instruction , (2) to explore how English teachers use Differentiated Instruction as a teaching approach in the classroom. Five English teachers from SMK 1 and SMK 2 Pariaman participated in this research. The data were gathered from observation checklists and interviews. The results suggested that the teachers understood the concept of Differentiated Instruction and knew how to identify their students’ needs but they lacked knowledge of how to differentiate interests in teaching process especially regarding the content differentiation. The implementation of the approach in the classroom showed that teachers differentiated the content based on students’ ability level and learning styles, while in the process, it was differentiated according to students’ ability level and product was differentiated based on students’ learning styles and interests.Keywords: differentiated instruction ; DI understanding; DI implementation.